Strengthening Islamic Financial Literacy and ZISWAF in the Regional Executive of Muhammadiyah Kubu Raya - Rahmat; Aiyub Anshori; Rini Elvri (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This activity aims to increase the insight, knowledge, and capacity of Islamic financial literacy as well as the management of ZISWAF within the Muhammadiyah Regional Executive (PDM) of Kubu Raya through an empowerment and mentoring program based on Participatory Action Research (PAR). Theoretical framework: The activity is grounded in Islamic financial literacy, focusing on understanding sharia-compliant asset management and optimizing ZISWAF for community empowerment, supported by the theory of community empowerment and active participation in financial transformation. Literature review: The study highlights Islamic financial literacy, including sharia-compliant wealth management and long-term financial planning, and the role of ZISWAF in social welfare. Previous research shows that improving financial literacy enhances financial management aligned with Sharia principles. Methods: The research uses a qualitative method with a Participatory Action Research (PAR) approach through three main stages: observation and reflection to identify literacy needs; planning and implementation of actions in the form of counseling and mentoring; and evaluation to assess the improvement of participants' understanding of ZISWAF-based financial planning. Results: The activity resulted in an increase in the understanding of the administrators and residents of Muhammadiyah PDM Kubu Raya regarding the urgency of Islamic financial literacy and the management of ZISWAF. Participants are able to understand and begin to implement Islamic financial planning, including the priority allocation of funds for zakat, infaq, alms, and long-term Islamic financial planning measures. Implications: The program strengthens the Muhammadiyah community's ability to manage sharia-based finances systematically, promoting sustainable financial practices and serving as a model for other Islamic communities. Novelty: The activity’s novelty lies in applying the PAR approach to Islamic financial literacy and ZISWAF education, making participants active learners and contributors to their financial planning, thus enhancing the program’s sustainability and relevance.